Continuing Professional Development among Indigenous teacher educators in the Institute of Teacher Education Rajang Campus, Sarawak Land of the Hornbill - Laily Yahya; Adam Prakash (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
This paper presents a Continuing Professional Development strategic plan of FUN-TASK-TICK communication course for Indigenous teacher educators in the Institute of Teacher Education Rajang Campus, Sarawak. The inspiration of the course is our response in support of the National Agenda Highly Immersive Program (HIP) as specified in the Malaysian Education Blueprint (2013-2025) focusing on strengthening the use of English Language for all. It emphasises the fundamental need to acquire the English Language to remain relevant in the global market. Recognising these initiatives and acknowledging the vision and mission of the campus as the leading organization for teacher education excellence, therefore this communication course is profoundly pertinent to address these challenges. Encapsulating these aspirations, this paper highlights the roadmap of the course encompassing the beliefs, participants’ learning styles, the training Model and theoretical underpinning the development of the course. Reflective Accelerated Learning Cycle is advocated to navigate the execution of the course. As a Continuous Professional Development pursuit, Continuous Quality Improvement plan 4Rs: Reflect, Revisit, Realign, and Reconstruct is proposed to accelerate their professional attitudes and dispositions.